Quartz sand flotation method

Through the quartz sand flotation method, including grinding, desilting, magnetic separation, flotation and acid leaching treatment, the problem of difficulty in removing quartz sand impurities in the prior art is solved, and the purification of high-purity quartz sand is achieved, reducing the environment and Human body hazards.

CN119456212AInactive Publication Date: 2025-02-18JIANGXI JIULING SILICON IND CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411683571.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing high-purity quartz purification process is difficult to effectively remove impurities in quartz sand, resulting in insufficient product purity.

Method used

The quartz sand flotation method is used, including grinding, desilting, magnetic separation, flotation and acid leaching treatment of quartz raw materials, removing impurities through flotation agents and acid leaching processes, and improving the purity of quartz sand.

Benefits of technology

It has achieved efficient removal of impurities in quartz sand, significantly improved the purity of ore, and eliminated chlorination and roasting, reducing the harm to the environment and the human body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119456212A_ABST
    Figure CN119456212A_ABST
Patent Text Reader

Abstract

The invention provides a quartz sand flotation method. The quartz sand flotation method comprises the following steps: grinding a quartz raw material to obtain coarse sand of 80-140 meshes; desliming and magnetically separating the coarse sand to obtain magnetically separated quartz fine sand; carrying out flotation on the magnetic separation quartz fine sand by using a flotation reagent so as to float out impurities such as gangue minerals and obtain quartz fine sand; carrying out acid leaching treatment on the quartz fine sand, and washing the quartz fine sand with pure water until the quartz fine sand is neutral to obtain high-purity quartz sand; wherein the flotation reagent comprises a GY-03 flotation reagent and a GY-04 flotation reagent; according to the method, minerals containing elements such as potassium, sodium and aluminum in the quartz raw material are removed through flotation, so that the purity of the ores is improved. And the flotation step is adopted, chloridizing roasting is omitted, and harm to the environment and the human body can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of quartz sand purification, and in particular to a quartz sand flotation method. Background Art

[0002] High-purity quartz is a high-purity quartz material, usually made from crystal, vein quartz, granite pegmatite and other minerals through fine purification. Its silicon dioxide (SiO2) content reaches more than 99.9%, and it is usually used as a raw material for semiconductors, photovoltaic materials and aerospace materials. The higher the purity of quartz sand, the stronger its insulation and corrosion resistance.

[0003] However, the current purification process for high-purity quartz is often acid leaching, chlorination roasting and other methods. The above methods can only remove some impurities on the surface of quartz sand and a part of gangue minerals, and lack the targeted removal of impurity elements. Summary of the invention

[0004] The present application provides a quartz sand flotation method which is beneficial for efficiently removing impurity elements.

[0005] In a first aspect, an embodiment of the present application provides a quartz sand flotation method, the quartz sand flotation method comprising:

[0006] Grinding the quartz raw material to obtain 80-140 mesh coarse sand;

[0007] Desludging and magnetic separation are performed on the coarse sand to obtain magnetically separated quartz concentrate sand;

[0008] Using a flotation agent to flot the magnetically separated quartz concentrate to float out impurities such as gangue minerals to obtain quartz concentrate;

[0009] The quartz sand is subjected to acid leaching treatment and then washed with pure water until it becomes neutral to obtain high-purity quartz sand;

[0010] Wherein, the flotation reagents include GY-03 flotation reagent and GY-04 flotation reagent;

[0011] The mass percentage content of the GY-03 flotation reagent includes: 0.04% sodium dodecyl sulfate, 3.04% acetic acid, 10.84% ​​mineral oil, 19.67% Kerosene, 10.79% sodium dodecyl sulfonate, 17.59% dodecyl trimethyl ammonium bromide, and 38.03% mixed solution 1;

[0012] The components of the mixed solution 1 include: 5.07% octylamine, 6.37% decylamine, 35.1%-36.2% dodecylamine, 6.81% tetradecylamine, 9.94% hexadecylamine, 8.87% oleylamine, 21.08%-22.18% octadecylamine, and 6.76% tallowamine;

[0013] The mass percentage content of the GY-04 flotation reagent includes: 5.5% sodium dihydrogen phosphate, 7.38% disodium dihydrogen pyrophosphate, 26.55% sodium hexametaphosphate, 13.22% (propylene glycol) bis (2-aminopropyl ether), and 47.35% mixed solution 2;

[0014] The components of the mixed solution 2 include: 19.62% hydroxypropyl starch, 20.49% sodium oleate, 42.19% sodium silicate, and 17.7% carboxymethyl cellulose.

[0015] According to the first aspect, in a possible implementation, the mass ratio of magnetic quartz concentrate to flotation reagent is: 200:(10.25-11).

[0016] According to the first aspect, in a possible implementation, the mass ratio of the GY-03 flotation agent to the GY-04 flotation agent is (9.50-10.00):(0.75-1.00).

[0017] According to the first aspect, in a possible implementation, in the step of using a flotation agent to float the magnetically separated quartz concentrate to float out impurities such as gangue minerals to obtain quartz concentrate, the flotation agent is added in 4 to 6 times, the interval between two adjacent additions of the flotation agent is 20 minutes, and the cumulative flotation time is 1.5h-2h.

[0018] According to the first aspect, in a possible implementation, the quartz sand flotation method further includes:

[0019] The ore is roasted and water-quenched and then crushed into blocks containing quartz, feldspar and mica;

[0020] The material block is crushed to a particle size less than 10 mm to obtain a quartz raw material.

[0021] According to the first aspect, in a possible implementation, in the step of crushing the ore into blocks containing quartz, feldspar and mica after roasting and water quenching, the roasting temperature is 1100° C. and the roasting time is 2 hours.

[0022] According to the first aspect, in a possible implementation, the step of grinding the quartz raw material to obtain 80-140 mesh coarse sand includes:

[0023] The quartz raw material is mixed with water to form a slurry with a concentration of 30%, and rod milled; wherein the rod mill medium is manganese steel with a length of 8 cm;

[0024] The rod-milled quartz raw material is mixed with water to form a slurry with a concentration of 32%, and then ball-milled; wherein the ball-milling medium is a steel ball with a particle size of 5 cm.

[0025] According to the first aspect, in a possible implementation method, after the quartz concentrate is subjected to acid leaching treatment, it is washed with pure water to neutrality to obtain high-purity quartz sand, and acid leaching is performed using a mixed acid formed by mixing hydrochloric acid, sulfuric acid, oxalic acid and hydrofluoric acid, and the mass ratio of the hydrochloric acid, sulfuric acid, nitric acid and hydrofluoric acid is 4:4:2:1.

[0026] According to the first aspect, in a possible implementation, in the step of subjecting the quartz concentrate to acid leaching and then washing it with pure water to neutrality to obtain high-purity quartz sand, the mass ratio of the quartz concentrate to the mixed acid is 1:2.

[0027] According to the first aspect, in a possible implementation, in the step of subjecting the quartz concentrate to acid leaching and then washing it with pure water to neutrality to obtain high-purity quartz sand, the acid leaching temperature is 100° C. and the acid leaching time is 3 hours.

[0028] The quartz sand flotation method provided in the present application removes minerals containing potassium, sodium, aluminum and other elements in the quartz raw material through flotation, thereby improving the purity of the ore. In addition, the flotation step is adopted and the chlorination roasting is eliminated, which can reduce the harm to the environment and human body. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0030] Figure 1 is a schematic flow chart of the quartz sand flotation method in the first embodiment;

[0031] Figure 2 It is a schematic flow chart of the quartz sand flotation method in the second embodiment. DETAILED DESCRIPTION

[0032] The words "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.

[0033] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.

[0035] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0036] The present application provides a quartz sand flotation method which is beneficial for efficiently removing impurity elements.

[0037] The present application embodiment provides a quartz sand flotation method, such as Figure 1 As shown, in the first embodiment, the quartz sand flotation method comprises the following steps:

[0038] Step S10, grinding the quartz raw material to obtain 80-140 mesh coarse sand;

[0039] By combining rod milling and ball milling, coarse sand that meets the requirements can be obtained; further, the particle size of the coarse sand can be guaranteed by screening, which provides a good foundation for the subsequent desludging, magnetic separation and flotation steps.

[0040] The quartz raw material is mixed with water to form a 30% concentration slurry, which is conducive to a more uniform dispersion of the quartz raw material during the grinding process. The slurry is rod-milled using manganese steel with a length of 8 cm as the rod mill medium. Manganese steel is very suitable for grinding hard materials such as quartz due to its high hardness and wear resistance. The purpose of the rod mill is to initially crush the quartz raw material and reduce its particle size. After rod milling, the quartz raw material is mixed with water again to form a 32% concentration slurry. The slurry concentration is adjusted to meet the needs of the ball milling process. The slurry is ball-milled using steel balls with a particle size of 5 cm as the ball mill medium. Steel balls also have high hardness and wear resistance, which can further crush the quartz raw material and make its particle size reach the required 80-140 mesh range.

[0041] After ball milling, the quartz raw material needs to be screened out by screening equipment to obtain the coarse sand that meets the particle size requirements. Screening equipment usually uses vibrating screens or rotary screens, which can effectively separate the ground quartz raw materials according to particle size. Through screening, it can ensure that the coarse sand obtained has a uniform particle size and meets the requirements of the subsequent flotation step. This helps to improve the flotation efficiency and the purity of the final product.

[0042] Screening equipment usually uses vibrating screens or rotary screens, which can effectively separate the ground quartz raw materials according to particle size. Through screening, it can ensure that the coarse sand obtained has a uniform particle size and meets the requirements of the subsequent flotation step.

[0043] It should be noted that, in this embodiment, the slurry concentration during rod milling and ball milling can be adjusted according to demand, so as to optimize the grinding process and improve the grinding efficiency and product quality.

[0044] Step S20, desludging and magnetically separating the coarse sand to obtain magnetically separated quartz concentrate sand;

[0045] Desludging is the process of removing fine-grained muddy impurities from coarse sand. These muddy impurities may affect the effect of subsequent magnetic separation and flotation, so they need to be removed before magnetic separation. Desludging is usually achieved by hydraulic classification or washing, using the action of water flow to separate fine-grained muddy impurities from coarse sand.

[0046] Magnetic separation is a process of separation using the difference in the magnetic properties of minerals. In quartz sand, some magnetic minerals (such as iron oxides, etc.) will affect the purity and quality of the final product, so they need to be removed by magnetic separation.

[0047] In this embodiment, gradient magnetic separation is used, that is, different magnetic field strength gradients are set to separate minerals with different magnetic properties. The first gradient is 10000GS, which is mainly used to remove weakly magnetic minerals; the second gradient is 20000GS, which is used to further remove strongly magnetic minerals.

[0048] Through gradient magnetic separation, the magnetic minerals in quartz sand can be effectively separated from the quartz particles to obtain purer magnetically separated quartz concentrate.

[0049] Step S30, using a flotation agent to flotate the magnetically separated quartz concentrate to float out impurities such as gangue minerals to obtain quartz concentrate;

[0050] Wherein, the flotation reagents include GY-03 flotation reagent and GY-04 flotation reagent;

[0051] The GY-03 flotation reagent combines sodium dodecyl sulfate, acetic acid, mineral oil, Kerosene (kerosene), sodium dodecyl sulfate, dodecyltrimethylammonium bromide and mixed solution 1, while the GY-04 flotation reagent contains sodium dihydrogen phosphate, disodium dihydrogen pyrophosphate, sodium hexametaphosphate, (propylene glycol) bis(2-aminopropyl ether) and mixed solution 2.

[0052] The exact mass percentages of the components in the GY-03 flotation agent are as follows: 0.04% sodium dodecyl sulfate, 3.04% acetic acid, 10.84% ​​mineral oil, 19.67% Kerosene, 10.79% sodium dodecyl sulfate, 17.59% dodecyltrimethylammonium bromide, and 38.03% mixed solution 1.

[0053] The detailed components of the mixed solution 1 include: 5.07% of octylamine, 6.37% of decylamine, 35.1% to 36.2% of dodecylamine, 6.81% of tetradecylamine, 9.94% of hexadecylamine, 8.87% of oleylamine, 21.08% to 22.18% of octadecylamine, and 6.76% of tallowamine.

[0054] The exact mass percentages of the components in the GY-04 flotation agent are as follows: 5.5% sodium dihydrogen phosphate, 7.38% disodium dihydrogen pyrophosphate, 26.55% sodium hexametaphosphate, 13.22% (propylene glycol) bis(2-aminopropyl ether), and 47.35% mixed solution 2.

[0055] The detailed components of the mixed solution 2 include: 19.62% hydroxypropyl starch, 20.49% sodium oleate, 42.19% sodium silicate, and 17.7% carboxymethyl cellulose.

[0056] The total mass ratio of magnetic quartz concentrate to flotation reagent is 200:(10.25~11), ensuring that the reagent can fully play its role.

[0057] The mass ratio of the two flotation agents GY-03 and GY-04 is set to (9.50~10.00):(0.75~1.00) to optimize the flotation effect.

[0058] The flotation reagent needs to be added gradually in 4 to 6 times, with a 20-minute interval between each addition to ensure that the reagent and the quartz concentrate are fully mixed and reacted. The total duration of the entire flotation process is controlled between 1.5 hours and 2 hours to achieve the best flotation effect.

[0059] Step S40, after subjecting the quartz concentrate to acid leaching treatment, washing with pure water until it becomes neutral, to obtain high-purity quartz sand;

[0060] The solution used for acid leaching is a mixture of hydrochloric acid, sulfuric acid, nitric acid and hydrofluoric acid. The mass ratio of these four acids is set to 4:4:2:1 to ensure that trace metal impurities in quartz can be removed efficiently.

[0061] Acid leaching is performed using a mixed acid formed by mixing hydrochloric acid, sulfuric acid, oxalic acid and hydrofluoric acid, wherein the mass ratio of the hydrochloric acid to the sulfuric acid is 4:4:2:1.

[0062] The prepared mixed acid is mixed with quartz concentrate, and the mass ratio of quartz concentrate to mixed acid is 1:2. This ratio can ensure that the acid leaching solution is in full contact with the quartz concentrate, thereby effectively removing impurities.

[0063] The acid leaching process was carried out at a temperature of 100°C for 3 hours. This condition setting helps to accelerate the chemical reaction and improve the removal efficiency of impurities.

[0064] After the acid leaching is completed, the quartz sand needs to be washed several times with pure water until the pH value of the washing liquid reaches neutral. This step is very important, as it can remove the acid and dissolved impurities remaining on the surface of the quartz sand and ensure the purity of the final product. The resistivity of pure water is 18.25 megohms

[0065] After washing, the quartz sand needs to be dried to remove excess moisture. Drying conditions (such as temperature and time) need to be adjusted according to specific circumstances to ensure the dryness and quality of the quartz sand.

[0066] In this embodiment, flotation is used to remove minerals containing potassium, sodium, aluminum and other elements in the quartz raw material, thereby improving the purity of the ore. In addition, the flotation step is adopted and the chlorination roasting is eliminated, which can reduce the harm to the environment and human body.

[0067] like Figure 2 As shown, in the second embodiment, before step S10, the following steps are also included:

[0068] Step S50, crushing the ore into blocks containing quartz, feldspar and mica after roasting and water quenching;

[0069] The ore is placed in a muffle furnace and roasted at 1100°C for 2 hours. The purpose of roasting is to change the physical and chemical properties of the ore, such as changing the mineral phase in the ore and removing some volatile impurities.

[0070] and forming or changing gas-liquid inclusions in ores.

[0071] After roasting, the ore is immediately taken out of the muffle furnace and quickly placed in water for quenching.

[0072] The purpose of water quenching is to use a sharp temperature change (from high temperature to low temperature) to break the expanded gas-liquid inclusions in the ore. These gas-liquid inclusions may expand due to the change of mineral phase during roasting, and break due to the sharp drop in temperature during water quenching, thereby exposing more mineral surfaces for subsequent processing.

[0073] After water quenching, the ore needs to be dried to remove excess water.

[0074] Step S60, crushing the material block to a particle size less than 10 mm to obtain quartz raw material.

[0075] The ore dried after water quenching is put into the double-roll crusher for crushing.

[0076] The double-roll crusher squeezes and crushes the ore through two relatively rotating rollers, thereby obtaining ore blocks containing quartz, feldspar and mica with a particle size of about 10 mm.

[0077] The purpose of crushing is to break the ore into smaller particles to facilitate the extraction and purification of quartz in subsequent steps.

[0078] In the first embodiment, the collected E ore is placed in a muffle furnace and roasted at 1100°C for 2 hours, and there is no requirement for the heating rate. While waiting for the roasting to be completed, it is quickly taken out for water quenching. The purpose of water quenching is to break the expanded gas-liquid inclusions for subsequent processing. Subsequently, the ore after water quenching and drying is placed in a double-roll crusher for crushing, and a quartz, feldspar, and mica ore with a particle size of about 10 mm can be obtained.

[0079] After the rough crushing, the ore is first manually selected to remove large feldspar and mica, which account for about 30% of the original ore (mass percentage content), and the remaining 70% is quartz ore (containing a very small amount of feldspar and mica, which can be removed by subsequent flotation acid leaching). The selected ore is ground. The grinding equipment is a rod mill and a ball mill. The conditions for rod milling include: the steel rod medium is manganese steel, the length is 8cm, and the ore pulp concentration is 30%; the conditions for ball milling include: the medium is steel ball, the particle size is 5cm, and the ore pulp concentration is 32%. After grinding, 80-140 mesh ore samples are screened out, and the ore samples below 80 mesh are continuously ground until the mesh size is all 80-140 mesh. After desludging and gradient magnetic separation, the first gradient is 10000GS, and the second gradient is 20000GS. The magnetically separated quartz concentrate accounts for about 32.29% of the original ore.

[0080] Take 200g of the prepared magnetically separated quartz concentrate and put it into a 0.75L flotation tank, adjust the pulp concentration to about 18%, and use flotation agents "GY-03" and "GY-04" for experiments. This experiment uses batch addition of agents, that is, after a single scraping, add the agent again and repeat until no impurities float out. This experiment added agents in an average of 5 times, and 9.5g of 100% concentration agent "GY-03" and 0.75g of "GY-04" were added in four times, and the cumulative flotation time was about 1.5h. The yield of quartz concentrate is about 90%.

[0081] Take 10g of the above quartz sand and put it into a polytetrafluoroethylene beaker, add 20g of mixed acid (the mass ratio of the mixed acid is hydrochloric acid, sulfuric acid, nitric acid and hydrofluoric acid is 4:4:2:1), put it into a vacuum box at 100℃ and leave it for 3h. Then take it out and wash it with 18.25 megohm pure water until it is neutral.

[0082] The experimental results are shown in the following table:

[0083] Ore Flotation sand High purity sand Lithium / ppm 0 0 0 Calcium / ppm 8.142 1.676 0 Magnesium / ppm 2.145 0.853 0.222 Iron / ppm 7.569 1.266 0.329 Sodium / ppm 15.642 6.552 2.288 Potassium / ppm 20.932 4.258 0 Aluminum / ppm 88.254 25.939 13.32 Manganese / ppm 0.236 0.09 0.048 Zinc / ppm 0.799 0.602 0 Lead / ppm 0.079 0 0 Copper / ppm 0.539 0.411 0 Phosphorus / ppm 0.343 0.138 0.023 Boron / ppm 0 0 0 Nickel / ppm 0 0 0 Chromium / ppm 1.39 0.397 0.029 Beryllium / ppm 0.002 0.001 0 Titanium / ppm 1.355 1.212 1.831 Total / ppm 147.427 43.395 18.09

[0084] It can be seen from the results that most impurities, especially potassium, sodium and aluminum, can be floated out by flotation with flotation agents, and the E ore can be purified into quartz sand with a purity of more than 99.998% by acid leaching.

[0085] In the second embodiment, the collected Pingjiang 2# ore is placed in a muffle furnace and roasted at 1100°C for 2 hours, and there is no requirement for the heating rate. While waiting for the roasting to be completed, it is quickly taken out for water quenching. The purpose of water quenching is to break the expanded gas-liquid inclusions for subsequent processing. Subsequently, the ore after water quenching and drying is placed in a double-roll crusher for crushing, and a quartz, feldspar, and mica ore with a particle size of about 10 mm can be obtained.

[0086] After the rough crushing, the ore is first manually selected to remove large feldspar and mica, which account for about 25% of the original ore (mass percentage content), and the remaining 75% is quartz ore (containing a very small amount of feldspar and mica, which can be removed by subsequent flotation acid leaching). The selected ore is ground. The grinding equipment is a rod mill and a ball mill. The conditions for rod milling include: the steel rod medium is manganese steel, the length is 8cm, and the slurry concentration is 30%; the conditions for ball milling include: the medium is steel ball, the particle size is 5cm, and the slurry concentration is 32%. After grinding, 80-140 mesh ore samples are screened out, and the ore samples below 80 mesh are continuously ground until the mesh size is all 80-140 mesh. After desludging and gradient magnetic separation, the first gradient is 10000GS, and the second gradient is 20000GS. The magnetically separated quartz concentrate accounts for about 29.34% of the original ore.

[0087] Take 200g of the prepared magnetically separated quartz concentrate and put it into a 0.75L flotation tank. Adjust the pulp concentration to about 18%. Use flotation agents "GY-03" and "GY-04" for experiments. This experiment uses batch addition of agents, that is, after a single scraping, add the agent again and repeat until no impurities float out. This experiment added agents in an average of 5 times, and 9.6g of 100% concentration agent "GY-03" and 0.95g of "GY-04" were added in four times. The cumulative flotation time was about 1.5h. The yield of quartz concentrate is about 83%.

[0088] Take 10g of the above quartz sand and put it into a polytetrafluoroethylene beaker, add 20g of mixed acid (the mass ratio of the mixed acid is hydrochloric acid, sulfuric acid, nitric acid and hydrofluoric acid is 4:4:2:1), put it into a vacuum box at 100℃ and leave it for 3h. Then take it out and wash it with 18.25 megohm pure water until it is neutral.

[0089] The experimental results are shown in the following table:

[0090] Ore Flotation sand High purity sand Lithium / ppm 0 0 0 Calcium / ppm 35.392 0 0 Magnesium / ppm 1.669 0.186 0 Iron / ppm 59.694 2.244 0.66 Sodium / ppm 210.72 7.245 2.302 Potassium / ppm 160.53 3.893 0.546 Aluminum / ppm 653.05 90.56 18.65 Manganese / ppm 2.241 0.115 0.134 Zinc / ppm 1.291 0.415 0.105 Lead / ppm 0 0 0 Copper / ppm 0.22 0.029 0 Phosphorus / ppm 15.784 0.329 0.487 Boron / ppm 0.335 0.025 0.06 Nickel / ppm 5.775 0.199 0.172 Chromium / ppm 0.81 0.155 0.109 Beryllium / ppm 2.292 0.342 0.335 Titanium / ppm 6.632 6.926 6.05 Total / ppm 1156.435 112.663 29.61

[0091] It can be seen from the results that most impurities, especially potassium, sodium and aluminum, can be floated out by flotation with flotation agents. Combined with acid leaching, Pingjiang No. 2 ore can be purified into quartz sand with a purity of more than 99.997%.

[0092] In the third embodiment, the collected Malaysian ore is placed in a muffle furnace and roasted at 1100°C for 2 hours, and there is no requirement for the heating rate. While waiting for the roasting to be completed, it is quickly taken out for water quenching. The purpose of water quenching is to break the expanded gas-liquid inclusions for subsequent processing. Subsequently, the ore after water quenching and drying is placed in a double-roll crusher for crushing, and a quartz, feldspar, and mica ore with a particle size of about 10 mm can be obtained.

[0093] After the rough crushing, the ore is first manually selected to remove large feldspar and mica, which account for about 22% (mass percentage) of the original ore, and the remaining 78% is quartz ore (containing a very small amount of feldspar and mica, which can be removed by subsequent flotation acid leaching). The selected ore is ground. The grinding equipment is a rod mill and a ball mill. The conditions for rod milling include: the steel rod medium is manganese steel, the length is 8cm, and the ore pulp concentration is 30%; the conditions for ball milling include: the medium is steel ball, the particle size is 5cm, and the ore pulp concentration is 32%. After grinding, 80-140 mesh ore samples are screened out, and the ore samples below 80 mesh are continuously ground until the mesh size is all 80-140 mesh. After desludging and gradient magnetic separation, the first gradient is 10000GS, and the second gradient is 20000GS. The magnetically separated quartz concentrate accounts for about 38.29% of the original ore.

[0094] Take 200g of the prepared magnetically separated quartz concentrate and put it into a 0.75L flotation tank. Adjust the pulp concentration to about 18%. Use flotation agents "GY-03" and "GY-04" to conduct experiments. This experiment uses batch addition of agents, that is, after a single scraping, add the agent again and repeat until no impurities float out. This experiment added agents in an average of 5 times, with a total of 9.90g of 100% concentration agent "GY-03" and 1.10g of "GY-04" added in four times. The cumulative flotation time is about 1.5h. The yield of quartz concentrate is about 85%. 2.2 Acid leaching experiment

[0095] Take 10g of the above quartz sand and put it into a polytetrafluoroethylene beaker, add 20g of mixed acid (the mass ratio of the mixed acid is hydrochloric acid, sulfuric acid, nitric acid and hydrofluoric acid is 4:4:2:1), put it into a vacuum box at 100℃ and leave it for 3h. Then take it out and wash it with 18.25 megohm pure water until it is neutral.

[0096] The experimental results are shown in the following table:

[0097] Ore Flotation sand High purity sand Lithium / ppm 0 0 0 Calcium / ppm 17.366 9.729 9.257 Magnesium / ppm 4.06 0.367 0.163 Iron / ppm 19.077 1.654 1.089 Sodium / ppm 33.881 13.284 10.754 Potassium / ppm 36.789 4.548 2.102 Aluminum / ppm 261.03 62.621 40.377 Manganese / ppm 1.017 0.924 0.389 Zinc / ppm 0.534 0.429 0.256 Lead / ppm 0 0 0 Copper / ppm 0.079 0.074 0.066 Phosphorus / ppm 1.486 0.519 0.121 Boron / ppm 0.163 0.157 0.148 Nickel / ppm 0.458 0.036 0.006 Chromium / ppm 1.126 0.264 0.039 Beryllium / ppm 0.255 0.094 0 Titanium / ppm 5.618 5.148 3.563 Total / ppm 382.939 99.848 68.33

[0098] It can be seen from the results that most impurities, especially potassium, sodium and aluminum, can be floated out by flotation with flotation agents, and the E ore can be purified into quartz sand with a concentration of more than 99.993% by acid leaching.

[0099] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the method of the present invention, addition of auxiliary steps, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A quartz sand flotation method, characterized in that: The quartz sand flotation method comprises: Grinding the quartz raw material to obtain 80-140 mesh coarse sand; Desludging and magnetic separation are performed on the coarse sand to obtain magnetically separated quartz concentrate sand; Using a flotation agent to flot the magnetically separated quartz concentrate to float out impurities such as gangue minerals to obtain quartz concentrate; The quartz sand is subjected to acid leaching treatment and then washed with pure water until it becomes neutral to obtain high-purity quartz sand; Wherein, the flotation reagents include GY-03 flotation reagent and GY-04 flotation reagent; The mass percentage content of the GY-03 flotation reagent includes: 0.04% sodium dodecyl sulfate, 3.04% acetic acid, 10.84% ​​mineral oil, 19.67% Kerosene, 10.79% sodium dodecyl sulfonate, 17.59% dodecyl trimethyl ammonium bromide, and 38.03% mixed solution 1; The components of the mixed solution 1 include: 5.07% octylamine, 6.37% decylamine, 35.1%-36.2% dodecylamine, 6.81% tetradecylamine, 9.94% hexadecylamine, 8.87% oleylamine, 21.08%-22.18% octadecylamine, and 6.76% tallowamine; The mass percentage content of the GY-04 flotation reagent includes: 5.5% sodium dihydrogen phosphate, 7.38% disodium dihydrogen pyrophosphate, 26.55% sodium hexametaphosphate, 13.22% (propylene glycol) bis (2-aminopropyl ether), and 47.35% mixed solution 2; The components of the mixed solution 2 include: 19.62% hydroxypropyl starch, 20.49% sodium oleate, 42.19% sodium silicate, and 17.7% carboxymethyl cellulose.

2. The quartz sand flotation method according to claim 1, characterized in that: The mass ratio of magnetic quartz concentrate to flotation agent is: 200:(10.25~11).

3. The quartz sand flotation method according to claim 2, characterized in that: The mass ratio of the GY-03 flotation agent to the GY-04 flotation agent is (9.50-10.00):(0.75-1.00).

4. The quartz sand flotation method according to claim 6, characterized in that: In the step of using a flotation agent to float the magnetically separated quartz concentrate to float out impurities such as gangue minerals to obtain quartz concentrate, the flotation agent is added in 4 to 6 times, the interval between two adjacent additions of the flotation agent is 20 minutes, and the cumulative flotation time is 1.5h-2h.

5. The quartz sand flotation method according to claim 1, characterized in that: The quartz sand flotation method also includes: The ore is roasted and water-quenched and then crushed into blocks containing quartz, feldspar and mica; The material block is crushed to a particle size less than 10 mm to obtain a quartz raw material.

6. The quartz sand flotation method according to claim 5, characterized in that: In the step of crushing the ore into blocks containing quartz, feldspar and mica after roasting and water quenching, the roasting temperature is 1100° C. and the roasting time is 2 hours.

7. The quartz sand flotation method according to claim 5, characterized in that: The step of grinding the quartz raw material to obtain 80-140 mesh coarse sand comprises: The quartz raw material is mixed with water to form a slurry with a concentration of 30%, and rod milled; wherein the rod mill medium is manganese steel with a length of 8 cm; The rod-milled quartz raw material is mixed with water to form a slurry with a concentration of 32%, and then ball-milled; wherein the ball-milling medium is a steel ball with a particle size of 5 cm.

8. The quartz sand flotation method according to claim 7, characterized in that: In the step of acid leaching the quartz concentrate, washing it with pure water until it becomes neutral to obtain high-purity quartz sand, acid leaching is performed using a mixed acid formed by mixing hydrochloric acid, sulfuric acid, oxalic acid and hydrofluoric acid, and the mass ratio of the hydrochloric acid, sulfuric acid, nitric acid and hydrofluoric acid is 4:4:2:

1.

9. The quartz sand flotation method according to claim 8, characterized in that: In the step of subjecting the quartz concentrate to acid leaching and then washing it with pure water until it becomes neutral to obtain high-purity quartz sand, the mass ratio of the quartz concentrate to the mixed acid is 1:

2.

10. The quartz sand flotation method according to claim 9, characterized in that: In the step of subjecting the quartz concentrate to acid leaching and then washing it with pure water until it becomes neutral to obtain high-purity quartz sand, the acid leaching temperature is 100° C. and the acid leaching time is 3 hours.

Citation Information

Cited By

  • Flotation reagent and preparation method thereof

    CN117380400A

  • Screening method of pegmatite type quartz potential raw material and preparation method of 4N8-grade high-purity quartz sand

    CN120518083A